Pengembangan Modul Ajar Fisika Berbasis Kaffah Learning untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa SMA - Syahrial A; Yulia Hasan; Muhammad Zuhdi; Muhammad Taufik (Kappa Journal, 2025)
This study aims to develop a physics teaching module based on Kaffah Learning and to examine its feasibility and effectiveness in improving high school students’ creative thinking skills. The development process employed the 4D model (Define, Design, Develop, and Disseminate). The Define stage included needs analysis through curriculum review and teacher interviews. In the Design stage, a module draft was constructed by integrating holistic values, contextual learning activities, and creative problem-solving tasks. The module was validated by material and media experts using a standardized feasibility assessment instrument. Quantitative data were analyzed using Aiken’s V index and the N-Gain test derived from pretest and posttest scores. The validation results indicated that all aspects of the module content appropriateness, language clarity, presentation, and graphical design achieved an Aiken’s V value of 0.83, categorized as highly feasible. A limited trial conducted with students at SMAN 3 Mataram showed an increase in the average score from 60 to 88 after using the module. The N-Gain analysis yielded a value of 0.38 (moderate category), indicating that the module effectively enhanced students’ creative thinking skills, although the improvement had not reached a high category. The application of Kaffah Learning was found to encourage idea exploration, reflection, and the integration of physics concepts with real-life contexts.This study concludes that the physics teaching module based on Kaffah Learning is highly feasible and reasonably effective in improving students’ creative thinking skills. These findings provide a foundation for further development of holistic learning materials in other physics topics.